Prescription Drug Coverage and Outcomes of Myeloma Therapy Among Medicare Beneficiaries - Olszewski, Adam J. (J Clin Oncol, 2018)
PURPOSE: Novel parenteral (bortezomib) and oral (lenalidomide) therapies have improved survival in myeloma, but the standard Medicare benefit covers only parenteral drugs. We examined the association between prescription drug coverage, receipt of therapy, and survival among Medicare beneficiaries with myeloma. METHODS: Using SEER-Medicare data, we identified enrollment in a Medicare Part D plan (PDP) or other creditable prescription drug coverage (OCC) among 9,755 beneficiaries who were diagnosed with myeloma in 2006 to 2011. We examined the receipt of active myeloma therapy and that of classic cytotoxic agents or bortezomib as first-line regimen and overall survival. We report relative risk (RR) for binary outcome comparisons and 3-year restricted mean survival time (RMST) ratios, with 95% CI, adjusting for baseline patient- and disease-related characteristics. Beneficiaries with diffuse large B-cell lymphoma, a cancer that is uniformly treated with parenteral chemotherapy, served as a comparison cohort. RESULTS: Compared with beneficiaries without prescription drug coverage, PDP or OCC enrollees were more likely to receive active myeloma care, and PDP enrollees were less frequently treated with parenteral agents (adjusted RR, 0.86; 95% CI, 0.80 to 0.93) or classic cytotoxic agents in particular (RR, 0.62; 95% CI, 0.51 to 0.76). Overall survival was significantly better for beneficiaries with PDP coverage (adjusted RMST ratio, 1.16; 95% CI, 1.11 to 1.20) or OCC (RMST ratio, 1.16; 95% CI, 1.12 to 1.21). In contrast, we observed no survival differences by prescription drug coverage status in the control cohort with lymphoma. CONCLUSION: Prescription drug coverage is associated with decreased use of classic cytotoxic chemotherapy and better survival among Medicare beneficiaries with myeloma, which suggests improved access to all existing treatment options. As oral targeted agents increasingly replace parenteral chemotherapy in oncology, adjustments in coverage policy are needed to ensure access to optimal treatment.